1992
DOI: 10.1111/j.1365-2222.1992.tb02829.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal variability of skin prick test results

Abstract: The skin prick test (SPT) is a commonly used procedure for assessing a specific sensitization. The longitudinal variability of test results is of interest for clinical as well as epidemiological investigations. The sensitization to four common aeroallergens (grass pollen, birch pollen, Dermatophagoides pteronyssinus, cat dander) is investigated within the framework of three consecutive SPTs at 11-month intervals for a population of 587 schoolchildren. The prevalence of sensitization based on a weal diameter of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…Four other studies [5][6][7][8] have investigated the longitudinal variability of SPTs among children. Unfortunately, direct comparison with our data is difficult because the populations studied had a different age profile and focused mainly on aeroallergens, and these studies used a different definition of a positive reaction.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Four other studies [5][6][7][8] have investigated the longitudinal variability of SPTs among children. Unfortunately, direct comparison with our data is difficult because the populations studied had a different age profile and focused mainly on aeroallergens, and these studies used a different definition of a positive reaction.…”
Section: Discussionmentioning
confidence: 98%
“…Historical population-based studies [5][6][7][8] have shown a high long-term stability of sensitization to some specific aeroallergens. However, these findings are based on cohorts followed nearly 20 years ago.…”
mentioning
confidence: 99%
“…The risk of allergy onset was conferred solely to the latter. It can be speculated that the former represents a state of transient SPT sensitisation [33,34] or a very early condition that over time progresses to increased allergen susceptibility. Could this be represented by the few subjects with insignificant symptoms?…”
Section: Discussionmentioning
confidence: 99%
“…The cut-off point for a positive test was 1.43 Magic-Lite (ML) units [16]. Measurement of total serum IgE was carried out by an enzyme allergosorbent test (Phadezym; Pharmacia, Uppsala, Sweden).…”
Section: Methodsmentioning
confidence: 99%